The Contribution of Arm Muscle Strength and Leg Muscle Explosive Power to Breaststroke Swimming Speed for a Distance of 20 Meters - Saputra, Muh. Rizky; Bismar, Ahmad Rum (Journal of Sport Education, Coaching, and Health (JOCCA), 2023)
This study aims to determine the contribution of arm muscle strength and leg muscle explosive power to the speed of 20-meter breaststroke swimming in students of the Faculty of Sports Sciences, Makassar State University. Types of descriptive research. The research variables consisted of independent variables, namely arm muscle strength and leg muscle explosive power, while the dependent variable was the speed of swimming breaststroke 20 meters. The population in this study was 30 people. The sampling technique is by random selection by lottery (simple random sampling). Data analysis techniques used are correlation analysis (r) and regression (R) at a significant level of 95% or α 0.05. Departing from the results of data analysis, this study concluded that: (1). there is arm muscle strength against the swimming speed of 20 meters breaststroke, obtained regression value (r) = 0.947 with a probability level (0.003) or α 0.05, for the value of R square (coefficient of determination) = 0.897. This translates to 89.7% of the speed of swimming the 20-meter breaststroke explained by arm muscle strength. (2) the explosive power of the leg muscles against the swimming speed of the 20-meter breaststroke, obtained regression value (r) = 0.881 with a probability level (0.000) or α 0.05, for the value of R square (coefficient of determination) = 0.775. This translates to 77.5% of the speed of swimming the 20-meter breaststroke. (3) arm muscle strength and muscle explosive power against the swimming speed of 20 meters breaststroke, obtained regression value (r) = 0.948 with probability level (0.008) or α 0.05, for R square value (coefficient of determination) = 0.899. This means that 89.9% of the speed of swimming in the 20-meter breaststroke is explained by the strength of the leg muscles and the explosive power of the leg muscles.